Efektivitas Pelatihan Kaligrafi Terhadap Peningkatan Keterampilan Menulis Arab Santri Pesantren Darul Arafah Raya - Muhammad Zaki Aditya (Jurnal Sathar, 2024)
Arabic writing skills are an essential ability for students in Islamic boarding schools (pesantren). This research aims to evaluate the effectiveness of calligraphy training in improving the Arabic writing skills of students at the Darul Arafah Raya Islamic Boarding School. The method used was a trial by comparing the Arabic writing abilities of students before and after attending calligraphy training. A total of 5 students were involved in this research. Their Arabic writing skills were assessed before attending the training. Then, their abilities were assessed after attending the calligraphy training (extracurricular) for 2 weeks. After the training was completed, their Arabic writing skills were reevaluated. The research results showed a significant improvement in the students' Arabic writing skills after attending the calligraphy training compared to before attending the training. It can be concluded that calligraphy training is effective in improving the Arabic writing skills of students at the Darul Arafah Raya Islamic Boarding School.